Valence bonds in planar and quasi-planar boron disks. Issue 2 (13th December 2018) - Patouossa, Issofa; Arvanitidis, Athanasios G.; Tshishimbi Muya, Jules; Nguyen, Minh Tho; Ceulemans, Arnout
Abstract : Valence bonds within the perimeter of disk-like boron clusters with a concentric topology follow simple 4 n and 8 n electron counting rules. Abstract : Planar and quasi-planar boron clusters with a disk-like shape are investigated in search of common bonding characteristics. Methods used involve molecular orbital calculations based on Density Functional Theory (DFT), and valence bond partitioning using Adaptive Natural Density Partitioning (AdNDP) analysis. For high-symmetry cases the proposed bonding schemes are confirmed using the group-theoretical induction method. The focus is on the electron occupation of delocalized in-plane 3-center and 4-center bonds. For disks consisting of concentric rings this inner electron count is found to be equal to a multiple of the vertex count of the inner polygon. For two concentric rings the multiplying factor is four, for three concentric rings it is eight. The appropriate bonding schemes are presented which explain these results. Some giant clusters with two hexagonal holes are also discussed.